"In-Office Balloon Sinus Ostial Dilation with Concurrent Antiplatelet and Anticoagulant Therapy for Chronic Rhinosinusitis without Nasal Polyps". (March 2020) - Higgins, Thomas S.; Öcal, Bülent; Adams, Ridwan; Wu, Arthur W.
Objective: Functional endoscopic sinus surgery (FESS) and balloon sinus ostial dilation (BSD) are well-recognized minimally invasive surgical treatments for chronic rhinosinusitis without nasal polyps (CRSsNP) refractory symptoms to medical therapy. Patients on antiplatelet and anticoagulant therapies (AAT) usually are recommended to discontinue their medications around the period of endoscopic sinus surgery. The goal of this study is to assess the clinical experience of BSD in CRSsNP patients with concurrent anticoagulant or antiplatelet therapy. Methods: A review of prospectively-collected clinical data from October 2012 to March 2017 were used to perform a cohort study of subjects with CRSsNP who met criteria for surgical intervention while on antiplatelet and anticoagulant therapy. Data were collected on demographics, details of the procedures, type of AAT used, pre- and postoperative 22-item Sino-Nasal Outcome Test (SNOT-22) scores, and complications. Results: Thirty-five patients underwent in-office BSD while on antiplatelet and/or anticoagulant therapy. The mean difference in pre- and postoperative SNOT-22 scores of 9.9 (SD 14.4, P  < .001) was both statistically significant and exceeded the minimal clinically important difference of 8.9. Absorbable nasal packing was used for persistent bleeding immediately post-procedure in two patients. Intraoperative bleeding was associated with aspirin 325 mg and warfarin. FESS was required for further management of chronic sinusitis in four patients after anticoagulant/antiplatelet therapy could be discontinued. There were no systemic complications. None of the patients experienced significant bleeding events postoperatively after leaving the office. Conclusion: In-office BSD appears to be a safe alternative to endoscopic sinus surgery in select patients who cannot discontinue antiplatelet and anticoagulant therapy. Levels of Evidence: IV